Pengetahuan, Sikap dan Dukungan Keluarga Lansia dengan Kunjungan Posyandu Lansia di Kelurahan Anduring Wilayah Kerja Puskesmas Ambacang Kota Padang - Novita, Marisa; Efitra, Efitra; Bahar, Idrawati; Tasman, Tasman; Suhaimi, Suhaimi (Jurnal Keperawatan Sehat Mandiri, 2023)
community, especially the elderly. Data from DKK Padang in 2020, Ambacang Community Health Center had the lowest coverage of elderly health services, namely (4.3%), the achievement target was (45%). The aim of this research is to determine the relationship between the level of knowledge, attitudes and family support for the elderly and visits to the Posyandu for the elderly in Anduring Village, Ambacang Health Center Working Area, Padang City in 2022. The design of this research is a cross sectional study. The research was conducted from January to June 2022. The population was 183 elderly people who visited the eight Posyandu for the Elderly in Anduring Village in the last 3 months (January to March 2022). The sample was 65 elderly people taken proportionally using accidental sampling technique. Data collection was carried out by questionnaire. Univariate data analysis with descriptive statistics in the form of frequency distribution. Bivariate analysis with Chi-square test. The research results showed that 49.2% of the elderly's knowledge was poor, 43.1% of the elderly's attitudes were negative, 44.6% of the elderly did not receive family support and 70.8% of the elderly visited the Elderly Posyandu regularly. There is a relationship between knowledge (p =0.024), attitude (p =0.017) and family support for the elderly (p =0.006). It is recommended for Community Health Center officers, especially nurses, to increase health promotion efforts about the importance of Posyandu for the Elderly by involving families with elderly people so as to increase visits by the elderly to Posyandu for the Elderly.